Peningkatan Pengetahuan Remaja Putri tentang Hipnoterapi dengan Musik Instrumentalia Melayu Jambi dalam Mengatasi Dismenore - Gustina, Gustina; Arifarahmi, Arifarahmi (Universitas Baiturrahim, 2025)
Dysmenorrhea or menstrual pain is a stabbing pain that is felt in the lower abdomen and thighs, this occurs due to an imbalance of the hormone progesterone in the blood, resulting in pain arising. Almost all women have felt interference during menstruation in the form of menstrual pain (dysmenorrhea) with various levels, ranging from just aches in the pelvis from the inside to extreme pain. Dysmenorrhea occurs in 50% to 90% of adolescent girls and women of reproductive age and is a major cause of absenteeism. The most complained and felt impact due to dysmenorrhea is limited physical activity, poor concentration and absenteeism in the teaching and learning process. Pharmacologically, pain can be treated with analgesic therapy, which is the most commonly used method of pain relief. This therapy can have an addictive impact and will provide dangerous drug side effects for patients. Non-pharmacologically, pain can be handled, one of which is with distraction techniques, namely the most effective distraction techniques to reduce pain is listening to classical music (mozart) and also back exercise. The purpose of this community service is to increase the knowledge of young women about hypnotherapy with Jambi Malay instrumental music in overcoming dysmenorrhea. The method / approach taken is to assess the knowledge of young women before and after education about hypnotherapy with Jambi Malay instrumental music in overcoming dysmenorrhea. After participating in a series of activities in accordance with the implementation plan, the results were: before good knowledge education was carried out 5 (23.8%) young women and less good 16 (76.6%) young women, after good knowledge education 21 (100%) people and less good 0 (0%).